Brain Neuroplasticity in Students Under Conditions of Intensive Learning: Molecular and Cellular Mechanisms (Texas Journal of Medical Science, 2026)
The objective of the present study is to systematize current knowledge regarding the specific molecular, cellular, and systemic mechanisms of neuroplasticity activated in the brains of students during periods of intensive learning, as well as to identify the endogenous and exogenous factors that modulate the efficacy of these processes